Politeness strategies and the effort to build the pragmatic competence through Cinderella - Rosita Ambarwati; Elin Tri Susilo (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2021)
This research is conducted to analyze the politeness strategy used by characters in Cinderella movie to strengthen pragmatic competence.  The objective of this research is to identify, (1) types of speech act used by characters of Cinderella movie in conveying politeness strategies (2) types of politeness strategies that are depicted by characters in Cinderella movie, and (3) to describe the relation of politeness strategy and pragmatic competence. The study is designed as descriptive qualitative research. The object of the study is a movie entitled Cinderella. Documentation and observation are the techniques to collect the data. This research is analyzed by using Spreadley Theory which includes four stages of analysis namely domain analysis, taxonomy analysis, componential analysis, and cultural theme analysis. The result of the analysis are (1) there are five types of speech acts used by the main characters of Cinderella movie in conveying politeness strategies. They are assertive, directive, commisive, expressive, and declarative. Directive speech act is becoming the most frequently used  by the main characters of this movie in conveying politeness strategies. (2) There are four types of politeness strategy that are depicted by the main characters in Cinderella movie. Those types are bald on – record strategy, positive politeness strategy, negative politeness strategy, and finally off – record strategy. The result shows that bald on – record strategy becomes the most frequently used strategy compared to the others. Politeness and pragmatic competence have a very close relationship. The importance of pragmatic competence can be strengthened through the choice of politeness strategies. Film as a mirror of a society is a good medium to analyze the sociocultural background of the utterance so that the purpose of the speaker's meaning can be realized appropriately.